Impact of Time to Castration Resistance on Survival in Metastatic Hormone Sensitive Prostate Cancer Patients in the Era of Combination Therapies - Wenzel, Mike; Preisser, Felix; Hoeh, Benedikt; Schroeder, Maria; Würnschimmel, Christoph; Steuber, Thomas; Heinzer, Hans; Banek, Severine; Ahrens, Marit; Becker, Andreas; Karakiewicz, Pierre I.; Chun, Felix K. H.; et al. (Frontiers in Oncology, 2021)
Background: To evaluate the impact of time to castration resistance (TTCR) in metastatic hormone-sensitive prostate cancer (mHSPC) patients on overall survival (OS) in the era of combination therapies for mHSPC. Material and Methods: Of 213 mHSPC patients diagnosed between 01/2013-12/2020 who subsequently developed metastatic castration resistant prostate cancer (mCRPC) 204 eligible patients were analyzed after having applied exclusion criteria. mHSPC patients were classified into TTCR <12 vs. 12-18 vs. 18-24 vs. >24 months and analyzed regarding OS. Moreover, further OS analyses were performed after having developed mCRPC status according to TTCR. Logistic regression models predicted the value of TTCR on OS. Results: Median follow-up was 34 months. Among 204 mHSPC patients, 41.2% harbored TTCR <12 months vs. 18.1% 12-18 months vs. 15.2% 18-24 months vs. 25.5% >24 months. Median age was 67 years and median PSA at prostate cancer diagnosis was 61 ng/ml. No differences in patient characteristics were observed (all p>0.05). According to OS, TTCR <12 months patients had the worst OS, followed by TTCR 12-18 months, 18-24 months and >24 months, in that order (p<0.001). After multivariable adjustment, a 4.07-, 3.31- and 6.40-fold higher mortality was observed for TTCR 18-24 months, 12-18 months and <12 months patients, relative to TTCR >24 months (all p<0.05). Conversely, OS after development of mCRPC was not influenced by TTCR stratification (all p>0.05). Conclusion: Patients with TTCR <12 months are at the highest OS disadvantage in mHSPC. This OS disadvantage persisted even after multivariable adjustment. Interestingly, TTCR stratified analyses did not influence OS in mCRPC patients.